Endoscopic Treatment of Frontal Sinus Mucoceles with Lateral Extension - Trimarchi, M. (Springer-Verlag, 2012)
To describe a new and useful criterion to identify endoscopically approachable lateral frontal sinus mucoceles. We retrospectively reviewed all patients diagnosed with frontal mucocele with lateral extension who underwent endoscopic sinus surgery (ESS) at the Department of Otorhinolaryngology, San Raffaele Scientific Institute over a 4 year period, from January 2008 to March 2012. We analyzed patient charts, pre- and post-operative imaging, operative reports, postoperative periods, and follow-up records. Our series is composed of seven patients, four males and three females, with a mean age of 56 years. Symptoms at presentation varied depending on the extent of mucocele growth and orbital and intracranial invasion. Mucocele extension medially to a virtual sagittal plane tangential to the medial side of the ocular globe was also evaluated with computed tomography, to determine the appropriateness and feasibility of an ESS procedure. After pre-operative investigations, patients underwent marsupialization of the mucocele with ESS. Postoperative follow-up ranged from 1 to 4 years. At present, all patients remain free of disease, as documented by radiological imaging. In defining endoscopically approachable lesions, it is essential to determine their extension beyond a virtual sagittal plane tangential to the medial side of the ocular globe. The success of the endoscopic procedures described was undoubtedly linked to the localization of the mucocele medial wall. This criterion is more important than the size of the mucocele, and accurate computed tomography evaluation can identify those mucoceles approachable with ESS, even if laterally extended.